The Effect of Education Level, Business Scale, Business Duration, and Business Turnover on the Financial Performance of MSMEs in Malang City - Jefrianus Petrus Ibar; Agnes Quartina Pudjiastuti; Yayuk Sulistyowati (International Research and Development for Human Beings (IRDH), 2026)
This study aims to examine and analyze the influence of education level, business scale, length of business, and business turnover on the financial performance of Micro, Small, and Medium Enterprises (MSMEs) in Malang City. Poor financial performance in the MSME sector is often attributed to the limited competency of the owners and the operational characteristics of the businesses. The research method used was a quantitative survey approach. The population in this study was MSMEs in Malang City, with a sampling technique used to obtain a sufficient number of respondents. Data collection was conducted through questionnaire interviews that had been tested for validity and reliability. The data analysis technique used was multiple linear regression analysis using SPSS software. The results showed that simultaneously, education level, business scale, length of business, and business turnover significantly influenced the financial performance of MSMEs in Malang City. Partially, the variables had a positive and significant effect on financial performance. This indicates that the higher the education level of the owner and the greater the turnover generated, the better the financial performance management tends to be. However, the variables did not show a significant effect in this study.